Individual terrorism - Coteño Muñoz, Alejandro (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: The attacks perpetrated on recent years by lone actors have aroused the interest of the lawmaker for the concept of individual terrorism. However, although it has been regulated in the last criminal reforms, a definition of it has not been positivized, a definition of it has not been provided in positive terms, but only in negative terms regarding collective terrorism. In this context, this study outlines the criteria to determine when an act of terrorism falls into individual terrorism and these tools are applied to three paradigmatic cases of what is generally known as lone wolves. Finally, three different classifications of the individual terrorist are provided to underpin a solid basis for an approach to their different levels of criminal dangerousness.